Factors Contributing to Students’ Speaking Anxiety: A Case Study at Students’ Junior High School - Wulandari Santoso; David D. Perrodin (CV. Creative Tugu Pena, 2021)
This article aimed of investigating the causes of students’ speaking anxiety at a Private Junior High School at Salatiga, Central Java. The method used case study. This study used a set of questionnaires distributed to sixty-six participants from grade 7 to grade 9. The participants were asked to choose the causes of their speaking anxiety offered in the questionnaire items according to their personal opinions. The questionnaire items were developed based on the literature used in this study. After that, the quantitative data were presented and then the data were described and interpreted. The results of this study revealed that the major factor contributing to the participants’ speaking anxiety was the concern about accuracy and grammar. Interestingly, the quantitative data of this study showed that a significant number of participants were less anxious especially when dealing with classroom settings and activities, and teachers. The result of the study was expected to contribute to student teachers and language teachers in general. This study helped them to be aware that speaking anxiety may exist among EFL students, hence they could develop their teaching methods and approaches in teaching speaking to minimize their students’ anxiety and to give more exposure to English for their students. Keywords: Speaking Anxiety, Factor Contributing Speaking, English Language Learning